2006
DOI: 10.1007/s10653-005-9023-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low molecular weight organic acids on adsorption and desorption of fluoride on variable charge soils

Abstract: The effect of four low molecular weight organic acids on F(-) adsorption by two variable charge soils was investigated using a batch method. The organic acids reduced F(-) adsorption through competition by the acids with F(-) for sorption sites. Oxalic and malonic acids, both of which have simpler chemical structures, were more effective than citric or malic acid. The effect of organic acids on F(-) adsorption was more prominent at higher pH values and with larger amounts of the organic acids. The desorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These acids, which have one or more carboxyl and hydroxyl groups, can form complexes with metal ions in soils and play an important role in soil processes such as mineral weathering, nutrient mobilization, and detoxification of Al (Hue et al , 1986; Bolan et al , 1994; Van Breemen et al , 2000). LMW organic acids can also change the surface chemical properties of variable charge soils (Xu et al , 2003; Xu et al , 2004a), and affect the adsorption of K + , NO 3 − and Cl − in these soils (Xu et al , 2004b; Xu et al , 2005a,b). Recently, the role of the organic acids in mineral weathering has been questioned, based on the premise that the concentration of the organic acids in soil solution is too small to have any significant effect on mineral dissolution rates (Drever & Stillings, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These acids, which have one or more carboxyl and hydroxyl groups, can form complexes with metal ions in soils and play an important role in soil processes such as mineral weathering, nutrient mobilization, and detoxification of Al (Hue et al , 1986; Bolan et al , 1994; Van Breemen et al , 2000). LMW organic acids can also change the surface chemical properties of variable charge soils (Xu et al , 2003; Xu et al , 2004a), and affect the adsorption of K + , NO 3 − and Cl − in these soils (Xu et al , 2004b; Xu et al , 2005a,b). Recently, the role of the organic acids in mineral weathering has been questioned, based on the premise that the concentration of the organic acids in soil solution is too small to have any significant effect on mineral dissolution rates (Drever & Stillings, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Begin and Fortin (2003) proposed that specific F − adsorption sites, associated with crystalline Al oxides and commonly shared F − and oxalate adsorption sites, involving less crystalline Al oxide phases, were present in a Spodosol A horizon. Xu et al, 2006 also observed that increased oxalate concentration reduced F − adsorption, suggesting competitive adsorption for exchange sites. Ligand exchange between oxalate and F − for common exchange sites was postulated to occur when oxalate concentration >> F − concentration, and that F − re-adsorption on these common sites was possible.…”
Section: Fluoride Additions and Aluminium Transportmentioning
confidence: 85%
“…Similar trends have been observed by Omueti and Jones (1977) for 15 acidic surface horizons and Zhang, Zhang, and Yu (1987) working with Ultisol subsoils. Fluoride sorption by soil has been observed to increase DOC concentrations in solution (Elrashedi and Lindsay, 1987;Totsche et al, 2000), suggesting competitive adsorption-desorption between various LMWOA, such as oxalate and F − for common adsorption sites (Xu, Wang, Zhao, Ji, & Zhang, 2006;Zutic & Stumm, 1984). Several studies have shown competitive adsorption between SO 4 2− , oxalate and F − for similar OH − exchange sites on soil metal oxides (Courchesne & Landry, 1994;Liu, He, Colombo, & Violante, 1999;Zhang et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This is because when the concentration of organic acid is lower, the pH and negative charges are significantly reduced, which promotes the desorption of heavy metals. However, with the increase of organic acid concentration, organic acids, Cd and Mn form ternary surface complexes on the soil surface, which promote adsorption and inhibit desorption (Xu et al, 2005). Under the fructose treatment, different dosages of fructose did not significantly reduce the soil pH, but the activation of heavy metals still had a positive effect on the first, third and seventh days.…”
Section: Frontiers In Environmental Sciencementioning
confidence: 96%